Determination of blood cholinesterase, neurobehavioral performance and genetic damage due to organophosphate exposure among male cocoa farmers in Pahang and Perak, Malaysia - Mohammad, Norsyazwani (2022)
Cocoa plantation farmers in Malaysia are continually being exposed to Organophosphate (OP) insecticide. Chlorpyrifos (group II) is an example of OP used in cocoa farms, and this chemical categorized as a moderately hazardous substance that may cause severe health effects to the plantation workers such as effects to the neurological system, reproductive system, hormonal changes and development of cancer. There are approximately 12,839 workers which is inclusive of cocoa farmers working with cocoa centre and independent smallholder cocoa farmers in Malaysia who are working in the cocoa plantations sector with the breakdown of 4,881 workers in Sabah, 5,613 workers in Sarawak and 2,345 (18.3%) workers in the Peninsular Malaysia. Cocoa farmers are considered at-risk for exposures to OP insecticides from activities such as mixing, spraying, cleaning, loading and disposal process at the workplace. It is imperative for studies to be implemented to find out how the exposure of cocoa farmers to OP pesticides may impact their health and safety, as there are currently no data available and focusing on that. Hence, the study was performed to assess the acute and chronic health effects among male cocoa farmers in Perak and Pahang, Malaysia over the period of exposure to OP in cocoa plantation. The blood cholinesterase level and neurobehavioral performance were used as indicators to determine the acute health effects, while genetic damage assessment was further conducted to determine the chronic health effects of the substance. This is a cross-sectional study among the male cocoa farmers who are working in the fields at the Cocoa Research and Development Centre in Jengka, Pahang and Bagan Datuk, Perak, Malaysia. This study is divided into three interlinked sub-studies: namely i) sociodemographic and occupational background distribution of respondents, ii) evaluation of OP exposure level, and iii) analysis of health effects linked to the OP exposure. A simple randomized method was applied in recruiting male cocoa farmer respondents (n=102). In Sub-study I, a structured questionnaire was administered to obtain individual, residential and occupational information. In Sub-study II, blood samples were collected via finger prick technique to evaluate acute OP exposure via determination of cholinesterase level. Calculations to estimate the intensity level of insecticide exposure were performed by using information obtained in sub-study 1 and used in an established algorithm. In Substudy III, Neurobehavioral Core Test Battery (NCTB) was used to measure the neurobehavioral performance. NCTB is one of the test batteries that are designed to assess the neurobehavioral performances on the human nervous system to assess effects due to neurotoxic chemicals exposures. There are seven subtests of NCTB which were included in this study. Buccal epithelial cell samples (n=97) were swabbed to identify genetic damage from chronic exposure to OP through comet and micronuclei (MN) assays. The average age of cocoa farmers was at 36.54±9.93 years old. The most common health symptoms facing by cocoa farmers were burning sensation in the face (57.8%), dizziness (51%), skin rashes and fatigue (38.2%), and headache and coughing (32.4%). In Substudy II, the median (interquartile range, IQR) estimation for intensity level of OP exposure among the cocoa farmers was 15.60 (16.0), with 52% of them were categorized as having a low-intensity level. The mean (SD) of blood cholinesterase levels among cocoa farmers group was 87.01 (13.15) in percentage which corresponding with the normal range. About 7.8% of cocoa farmers had abnormal levels. OP exposure had given poor performance on motor functionality and manual dexterity of cocoa farmers. In logistic regression, factors such as length of tenure showed statistically significant contribution to the performance on visual-motor speed (adjusted odds ratio (AOR) 0.18, 95% confidence interval (CI), 0.05-0.66) and motor steadiness (AOR 0.14; 95%CI, 0.04-0.54). In comparison, the age variable was contributing significantly to the reporting of manual dexterity performance (AOR 0.11; 95%CI, 0.01-1.01). In Sub-study III, the comet tail length values ranged between 12.06 and 35.27 μm (mean: 22.63 μm), whereas the percentage of DNA in the tail ranged between 16.79% and 53.69% (mean: 33.82%). Cocoa farmers reported an average MN frequency (per 1000 cells) with 8.51±3.99. Meanwhile, the blood cholinesterase level (odds ratio (OR) -0.12, 95% confidence interval (CI), -0.20- (-0.66) , p<0.01 and OR -0.13; 95%CI, -0.23- (-0.04), p<0.01), smoking duration (OR -0.23; 95%CI, -0.43- (-0.02), p<0.05), and appropriate personal protective equipment (PPE) (OR -10.14; 95%CI, -17.55- (-2.72), p<0.01), were among the significant predictive factors that contributed to 13% of the comet assay formation (e.g. comet tail length and the percentage of DNA in the tail). On the other hand, approximately 20.8% of MN frequency variation were explained by age (OR 0.10; 95%CI, -0.01-0.20), p<0.05), BMI (OR 0.26; 95%CI, 0.09-0.43), p<0.01), smoking habit (OR 5.19; 95%CI, 2.07-8.32), p<0.01) and smoking duration (OR -0.23; 95%CI, -0.37-(-0.08), p<0.01) among the cocoa farmers. In summary, the cocoa management has established good labour practices and guidelines for cocoa farmers to follow when handling pesticides. This is evidenced by the fact that majority of cocoa farmers had normal blood cholinesterase levels despite being constantly exposed to OP as part of their work. Most of them were slightly exposed to pesticides, but some of them showed poor motor functionality and manual dexterity. There are other factors might contribute to poor motor functionality and manual dexterity such as the environment, genetics and their lifestyle. This study suggests that the neurobehavioral assessments and genetic damage measurements conducted have provided insight into the need for early detection and screening of minor exposures to OP in cocoa farmers. The management need to provide necessary chemical-resistant PPE to cocoa farmers such as nitrile glove and respirator with filter. Besides there are also necessary to implement periodically monitoring health risk among cocoa farmers in the future.